Longitudinal circulating tumor DNA analysis during treatment of locally advanced resectable gastric or gastroesophageal junction adenocarcinoma: the PLAGAST prospective biomarker study - Aziz Zaanan; Audrey Didelot; Chloé Broudin; George Laliotis; Erik Spickard; Punashi Dutta; Aurélien Saltel-Fulero; Francesco Giulio Sullo; Margot Pizzamiglio; Antoine Mariani; Widad Lahlou; Meenakshi Malhotra; et al. (Nature Communications)
Abstract Patients with locally advanced resectable (LAR) gastric/gastroesophageal junction (G/GEJ) adenocarcinomas have a high recurrence risk despite pre- and post-operative treatment. In the PLAGAST prospective study (NCT02674373), we investigated the ability of circulating tumor DNA (ctDNA) to predict treatment response and improve risk stratification. Plasma samples were prospectively collected before neoadjuvant therapy (NAT), during-NAT, post-NAT, and post-surgery. The primary endpoint was recurrence-free survival (RFS), and the secondary endpoints were overall survival (OS), tumor regression grade (TRG), and pathological tumor stage. ctDNA positivity decreased over these four therapeutic timelines (69.6%, 51.2%, 26.8%, and 20%, respectively). ctDNA-positivity was associated with significantly worse outcomes during-NAT (RFS: HR = 6.17, P = 0.002; OS: HR = 4.71, P = 0.022), post-NAT (RFS: HR = 5.26, P = 0.001; OS: HR = 7.35, P = 0.001) and after surgery (RFS: HR = 12.94, P < 0.0001; OS: HR = 14.54, P < 0.0001). Patients with early ctDNA clearance during NAT had better outcomes compared to those who cleared ctDNA post-NAT, while patients who remained ctDNA-positive pre-, during-, and post-NAT had worse outcomes (RFS: HR = 18.57, P = 0.01; OS: HR = 16.06, P = 0.007). Our data suggests that longitudinal ctDNA monitoring is prognostic of patient outcomes and may guide therapeutic decision-making in patients with LAR G/GEJ adenocarcinoma.